Coping Mechanisms of Stress: The Impact on Online Purchase Impulsivity - Maharani, Silvina Angelia Dwi; Utami, Nanda Putri (Journal of Business, Management, and Social Studies, 2023)
The coping mechanisms of stress and their impact on online purchase impulsivity are essential in understanding consumer behavior in the digital age. This research investigates the relationship between stress, the form of coping strategies, and impulsive online purchasing, addressing the gap in the existing literature. Next, to determine which is the most effective between self-control failure and self-reward as coping mechanisms of stress that can trigger online impulsive buying. Using a survey-based approach conducted online with a 5-Likert scale, assessed by 25 survey items. A sample-to-item sampling method to collect a diverse sample of consumers in Indonesia uses a 5 to 1 ratio. The findings reveal that people in their productive age tend to experience this circumstance, resulting in a positive correlation between stress, self-reward, self-control failure, and online impulsive purchasing. However, it found that stress does not directly affect impulsive buying while coping mechanisms significantly impact this relationship. The conclusion emphasizes the relationship of the variables that may be used to develop a suitable marketing strategy and enhance employees’ performances.